2018
DOI: 10.1113/ep086815
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a radiotelemetric recording technique in mice to investigate gastric slow waves: Modulatory role of putative neurotransmitter systems

Abstract: The mouse is the most commonly used species in preclinical research, and isolated tissues are used to study slow waves from the interstitial cells of Cajal-smooth muscle syncytium of the gastrointestinal tract. The aim of this study was to establish a radiotelemetric technique in awake mice to record gastric myoelectric activity from the antrum to gain insight into the effects of endogenous modulatory systems on slow waves. Under general anaesthesia, two biopotential wires from a telemetry transmitter were sut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…To date, only limited information is available regarding DFA of GMA, probably because the time series of EGG recordings in humans have a short-duration. With the advent of radiotelemetric technology, long-term GMA from the antrum has been recorded in different species (Percie du Sert et al, 2010;Rudd et al, 2018;Wang et al, 2018). Theoretically, the observed periodic trend in GMA may invalidate the power-law scaling behavior (Hu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only limited information is available regarding DFA of GMA, probably because the time series of EGG recordings in humans have a short-duration. With the advent of radiotelemetric technology, long-term GMA from the antrum has been recorded in different species (Percie du Sert et al, 2010;Rudd et al, 2018;Wang et al, 2018). Theoretically, the observed periodic trend in GMA may invalidate the power-law scaling behavior (Hu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Using state-of-the-art radiotelemetric technology, our previous studies successfully recorded the GMA from freely moving ferrets, shrews and mice (Percie du Sert et al, 2010;Lu et al, 2014;Tu et al, 2017;Wang et al, 2018). In the ferrets, analysis of the DF and power partition of GMA revealed that GMA could be disrupted by emetics such as apomorphine (Percie du Sert et al, 2009a), cisplatin (Percie du Sert et al, 2009a), and exendin-4 (Lu et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…In the acute and chronic experiments, the existence of a DF was used as a criterion to include or reject recorded GI myoelectric signals. This criterion was based on prior studies involving awake behaving ferrets, dogs and mice [14, 2022] that described the DF as a characteristic and consistent peak in the power spectrum of myoelectric signals recorded across the stomach. Five animals in the acute study displayed a DF in the GI myoelectric signals for at least one gastric segment and the intra-subject variability of the DF (across paddles) was low.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute and chronic experiments, the existence of a DF was used as a criterion to include or reject recorded GI myoelectric signals. This criterion was based on prior studies involving awake behaving ferrets, dogs and mice [14,[19][20][21] that described the DF as a characteristic and consistent peak in the power spectrum of myoelectric signals recorded across the stomach. Five animals in the acute study displayed a DF in the GI myoelectric signals for at least one gastric segment and the intra-subject variability of the DF (across paddles) was low.…”
Section: Discussionmentioning
confidence: 99%